Development of learning media based on the class safari website (microsite) on the material i love the environment around grade 1 elementary school students - Hermawati, Desi; Sumarmi, Sumarmi; Mardhatillah, Mardhatillah; Dewi, Radeni Sukma Indra; Arifin , Slamet (Jurnal Bidang Pendidikan Dasar, 2025)
This study aims to develop a microsite-based learning media on the topic "I Love the Environment" for 1st grade elementary school students. The research method used is the Richey and Klein Research and Development (R&D) model, which consists of three stages: design, product development, and evaluation. The developed microsite product was declared very feasible based on expert validation results, with the following percentages: material experts 91%, language experts 96%, and media experts 92%. The trial results showed that this media is effective in providing convenience for teachers and students with an interesting, innovative, and interactive presentation. In addition, this media has been proven to improve student learning outcomes, as indicated by an increase in the average score from 50.3 (pretest) to 85 (posttest).